If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14+(-9)+(-12)=0
We simplify the equation to the form, which is simple to understand
14+(-9)+(-12)=0
Remove unnecessary parentheses
+14-9+(-12+)=0
Remove unnecessary parentheses
+14-9-12=0
We move all terms containing to the left and all other terms to the right.
0=0-14+9+12
We simplify left and right side of the equation.
0=+7
0=7
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| -3a^3b(9a^5+5ab-b^3)= | | 7(3a-x)=3b | | 51+(-104)+(-78)= | | 3x-7/4=2 | | 9x-5.5=7x+3.5 | | 12+[4+(-9)]= | | 15x+8y=130 | | [-16+(-6)]+4= | | 25x-4(4x+6)=-70 | | v=(x+3)(2x-5)(x-4) | | 4x+13=12x-3 | | (2x+y)+(5x+y)=80 | | 10-3x=2x-65 | | .4x+1.5y+6z=29.5 | | -4+8(1+5k)=-28 | | 2y^6+7xy^3+6x^2=0 | | Sqrt(x)=5 | | 0.15x+0.05(10-x)=0.10(23) | | 3(4x-2)-10=8 | | 0.5x^2-210x+38136=0 | | -22=7(5y+8) | | 3p+2q=-2 | | 8(1-3n)=25 | | 6z^4+z^2-1=0 | | 3x=1x+10 | | -16+x=-14 | | f(-t)=5x^2-9x-7 | | 27=5s-7s | | -2f(3f-5)= | | 25=10+ | | 10x^2+14x+3=0 | | y=2-lx+1l |